A polymer precursor ceramic thin film thermocouple and preparation method thereof

By adopting polymer precursor ceramic film thermocouple and vacuum pyrolysis technology, the problem of film temperature sensor peeling caused by mismatch in the thermal expansion coefficients of ceramic substrates and metal materials in the prior art is solved, and stable operation and excellent electrical performance are achieved in high-temperature environments.

CN119085875BActive Publication Date: 2025-03-14ZHONGBEI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411578004.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing precursor ceramic thin film sensors are prone to fall off due to the mismatch of the thermal expansion coefficients of the ceramic substrate and the metal material, and the bonding force of the sensitive layer and the substrate interface is reduced under the action of impact and vibration, and the film temperature sensor may break.

Method used

A polymer precursor ceramic film thermocouple is used, which includes an A electrode and a B electrode. The A electrode is made of a mixed polysilazane solution, a nanocomposite powder and a xylene solution. The nanocomposite material is made of a mixed indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; the B electrode is made of a mixed polysilazane solution, an indium oxide nanopowder and a xylene solution. The precursor ceramic film thermocouple was prepared by vacuum pyrolysis, and the protective layer precursor layer was prepared by pulsed laser deposition.

Benefits of technology

The thermal expansion coefficient of ceramic substrate and non-metallic materials is matched. The film thermocouple is not easy to break, the temperature resistance can reach above 1600℃, and has excellent high-temperature electrical characteristics and strong oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119085875B_ABST
    Figure CN119085875B_ABST
Patent Text Reader

Abstract

The invention aims to provide a polymer precursor ceramic thin film thermocouple and a preparation method thereof, belonging to the technical field of temperature sensors. The polymer precursor ceramic thin film thermocouple comprises an A electrode and a B electrode, one end of the A electrode and one end of the B electrode are arranged to intersect and overlap to form a hot node, and one end of the A electrode away from the hot node and one end of the B electrode away from the hot node are both provided with welding points; each welding point is connected with a lead wire, and the lead wire is used to output a signal; the A electrode is made by mixing a polysilazane solution, a nanocomposite material powder and a xylene solution, and the nanocomposite material is made by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; the B electrode is made by mixing a polysilazane solution, indium oxide nanopowder and a xylene solution; it has high-temperature electrical characteristics and strong anti-oxidation characteristics, and the thin film thermocouple is not easy to break; the temperature resistance can reach above 1600°C, and the problem that the existing thin film temperature sensor is prone to breakage and falling off is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of temperature sensors, and in particular relates to a polymer precursor ceramic film thermocouple and a preparation method thereof. Background Art

[0002] With the continuous improvement of the thrust-to-weight ratio of aircraft engines, the surface temperature of engine blades has reached 1500°C, which makes it quite difficult to monitor the distribution state of the surface temperature of engine blades in real time. Polymer-derived Ceramics (PDC) have the advantages of strong thermal shock resistance and high temperature resistance, and are cheap; its precursor is generally a liquid, which can be made into a slurry film by direct writing, micro-jet printing, screen printing and other methods, and then heated, cured, cross-linked, and pyrolyzed to obtain a ceramic film; the ceramic film has the characteristics of high sensitivity, adjustable, thin film patterning and convenient film formation. In addition, polymer precursor ceramics are semiconductors, and their resistance decreases with increasing temperature, and has a certain functional relationship. This thermal sensitive property can be used to make thin film temperature sensors.

[0003] Existing precursor ceramic thin film sensors are prone to falling off due to the mismatch in thermal expansion coefficients between the ceramic substrate and the metal material. In addition to thermal effects, thin film temperature sensors must also be able to withstand the impact and vibration loads of the engine. Due to the presence of holes and gaps at the interface between the sensitive layer and the substrate, the bonding force between the sensitive layer and the substrate interface is reduced under the action of impact and vibration, and the thin film temperature sensor may break. In addition, most of the current precursor ceramic materials are prepared into bulk sensors, which are not suitable for thin film temperature measurement and have great limitations. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a polymer precursor ceramic thin film thermocouple and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A polymer precursor ceramic thin film thermocouple, used for monitoring the surface temperature of a hot component; the polymer precursor ceramic thin film thermocouple comprises an A electrode and a B electrode, one end of the A electrode and one end of the B electrode are arranged to intersect and overlap to form a hot node, and one end of the A electrode away from the hot node and one end of the B electrode away from the hot node are both provided with a welding point;

[0007] Each of the welding points is connected to a lead wire, and the lead wire is used to output a signal;

[0008] The A electrode is made by mixing a polysilazane solution, a nanocomposite powder and a xylene solution;

[0009] The B electrode is made by mixing polysilazane solution, indium oxide nanopowder and xylene solution;

[0010] The nanocomposite material is prepared by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol.

[0011] Further optionally, in the A electrode, the mass fraction of the polysilazane solution is M A1 , the mass fraction of the nanocomposite powder is M A2 , the mass fraction of the xylene solution is M A3 , the M A1 、M A2 and M A3 Satisfaction: 20% ≤ M A1 ≤30%, 20% <M A2 ≤30%, 40%≤M A3 ≤60%;

[0012] In the B electrode, the mass fraction of the polysilazane solution is M B1 The mass fraction of the indium oxide nanopowder is M B2 , the mass fraction of the xylene solution is M B3 , the M B1 、M B2 and M B3 Satisfaction: 20% ≤ M B1 ≤30%, 20% <M B2 ≤30%, 40%≤M B3 ≤60%.

[0013] Further optionally, in the A electrode, the mass ratio of the polysilazane solution, the nanocomposite powder and the xylene solution is 1:1:2; in the B electrode, the mass ratio of the polysilazane solution, the indium oxide nanopowder and the xylene solution is 1:1:2.

[0014] Further optionally, in the nanocomposite material, the average particle size of the indium oxide nanopowder is d1, the average particle size of the zinc oxide powder is d2, and d1 and d2 satisfy: 50nm≤d1≤100nm, 20nm≤d2≤100nm;

[0015] In the B electrode, the average particle size of the indium oxide nanopowder is d3, and the d3 satisfies: 20nm≤d3≤20um.

[0016] Further optionally, the thickness of the A electrode is H A , the thickness of the B electrode is H B , the H A and H B Meet: 2um <HA ≤100um, 2um <H B ≤100um.

[0017] Further optionally, the solder joint is made by sintering a conductive paste, and the conductive paste is a polysilazane solution filled with titanium diboride nanopowder;

[0018] The lead wire is a filamentous structure, the lead wire is a platinum wire, and the diameter of the lead wire is d0, and d0 satisfies: 160um≤d0≤240um.

[0019] Further optionally, d0=200um.

[0020] A method for preparing a polymer precursor ceramic thin film thermocouple, wherein the polymer precursor ceramic thin film thermocouple is any one of the polymer precursor ceramic thin film thermocouples described above; the preparation method comprises:

[0021] S1. Pretreatment: cleaning and drying the alumina ceramic sheet;

[0022] S2, preparation of the nanocomposite powder: mixing the indium oxide nanopowder and the zinc oxide powder according to a first preset mass ratio k1, mixing the mixed powder and anhydrous ethanol according to a second preset mass ratio k2 and placing the mixed powder in a ball mill tank of a ball mill; controlling the ball mill to grind, and drying the mixture to obtain the nanocomposite powder; the speed of the ball mill during grinding is a preset speed n, and the grinding time is a first preset time t1; the temperature during the drying process is a first preset temperature T1;

[0023] Wherein, the k1, k2, n, t1 and T1 satisfy: 3≤k1≤5, 0.1≤k2≤1, 1600rpm≤n≤2400 rpm, 4h≤t1≤6h, 80℃≤T1≤120℃;

[0024] S3, preparation of mixed slurry A and mixed slurry B: the polysilazane solution, the nanocomposite powder and the xylene solution are mixed according to a third preset mass ratio k3 to prepare mixed slurry A; the polysilazane solution, the indium oxide nanopowder and the xylene solution are mixed according to a fourth preset mass ratio k4 to prepare mixed slurry B;

[0025] Wherein, k3 and k4 satisfy: 1:1:3≤k3≤1:1:1, 1:1:3≤k4≤1:1:1;

[0026] S4, preparation of polymer ceramic precursor A slurry and B slurry: magnetically stirring the A mixed slurry at room temperature to obtain polymer ceramic precursor A slurry; magnetically stirring the B mixed slurry at room temperature to obtain polymer ceramic precursor B slurry;

[0027] S5, preparation of the A electrode and the B electrode: using the Weissenberg direct writing process, directly writing the polymer precursor ceramic A slurry on the alumina ceramic sheet, and directly writing the polymer precursor ceramic B slurry on the alumina ceramic sheet; then placing the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written in a vacuum drying oven for heating and curing treatment, and then placing it in a vacuum tube furnace for sintering to obtain the A electrode and the B electrode;

[0028] S6, preparation of the solder joint: mixing titanium diboride nanopowder and polysilazane solution according to a fifth preset mass ratio k5 to obtain a conductive paste, placing the conductive paste on the alumina ceramic sheet and sintering to obtain the solder joint; electrically connecting the solder joint and the lead wire and placing them in a vacuum tube furnace for sintering;

[0029] Wherein, k5 satisfies: 1:3≤k5≤1:1.

[0030] Further optionally, in S5, the alumina ceramic sheet on which the polymer precursor ceramic A slurry and B slurry are directly written is placed in a vacuum drying oven for heating and curing treatment, and the temperature during the heating and curing treatment is a second preset temperature T2, and the duration is a second preset duration t2;

[0031] Wherein, the T2 and t2 satisfy: 100°C≤T2≤300°C, 0.4h≤t2≤0.6h;

[0032] Placing the alumina ceramic sheet on which the polymer precursor ceramic A slurry and B slurry are directly written in a vacuum tube furnace for sintering comprises:

[0033] First, the temperature is raised to a third preset temperature T3 at a preset heating rate v1, and kept at the temperature for a third preset time t3, during which the polymer precursor ceramic slurry A and the polymer precursor ceramic slurry B undergo an organic-to-inorganic transformation and generate an amorphous ceramic;

[0034] Secondly, the temperature is raised to a fourth preset temperature T4 at a preset heating rate v1, and kept at the temperature for a fourth preset time t4, during which the amorphous ceramic undergoes phase separation and crystallization, thereby generating a polycrystalline ceramic;

[0035] Finally, the temperature is lowered to room temperature at a preset cooling rate v2;

[0036] Wherein, the v1 and v2 satisfy: 3℃ / min≤v1≤7℃ / min, 3℃ / min≤v2≤7℃ / min; the T3 and t3 satisfy: 900℃≤T3≤1100℃, 3h≤t3≤5h; the T4 and t4 satisfy: 1400℃≤T4≤1800℃; 3h≤t4≤5h.

[0037] Further optionally, the S5 further includes:

[0038] The alumina ceramic sheet with the A electrode and the B electrode directly written thereon is placed in a vacuum tube furnace for annealing at high temperature, so that a layer of oxidation phase is formed on the surface of the A electrode and the surface of the B electrode; the temperature during the annealing is the fifth preset temperature T5, and the duration is the fifth preset duration t5;

[0039] Wherein, the T5 and t5 satisfy: 1000°C≤T5≤1400°C, 8h≤t5≤12h.

[0040] Further optionally, in S6, the temperature when the solder joint and the lead are electrically connected and placed in a vacuum tube furnace for sintering is a sixth preset temperature T6 and the duration is a sixth preset duration t6;

[0041] Wherein, T6 and t6 satisfy: 700°C≤T6≤900°C, 0.5h≤t6≤1.5h.

[0042] Further optionally, after S6, the step further includes:

[0043] S7, preparation of a protective layer precursor layer: titanium diboride nanopowder and YSZ nanopowder are mixed according to a sixth preset mass ratio k6 and added to a polysilazane solution, and placed in a vacuum drying oven for heating and curing treatment to obtain a protective layer precursor; the temperature during the heating and curing treatment is the seventh preset temperature T7, and the duration is the seventh preset duration t7;

[0044] The protective layer precursor is used as a target material, and is deposited on the top surface of the A electrode and the top surface of the B electrode by pulse laser, and then vacuum pyrolysis is performed to obtain a protective layer precursor layer; during the vacuum pyrolysis, the temperature is increased to an eighth preset temperature T8 at a preset heating rate v1 and maintained at the temperature for an eighth preset time t8;

[0045] Among them, the k6 satisfies: 3:1≤k6≤5:1; the T7 and t7 satisfy: 100℃≤T7≤300℃, 0.4h≤t7≤0.6h; the v1 satisfies: 3℃ / min≤v1≤7℃ / min; the T8 and t8 satisfy: 1400℃≤T8≤1800℃, 3h≤t8≤5h.

[0046] Further optionally, the thickness of the protective layer precursor layer is H C , the H C Meet: 2um <H C ≤100um.

[0047] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0048] (1) The polymer precursor ceramic thin film thermocouple of the present invention comprises an A electrode and a B electrode, wherein the A electrode is prepared by mixing a polysilazane solution, a nanocomposite material powder and a xylene solution, wherein the nanocomposite material is prepared by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; the B electrode is prepared by mixing a polysilazane solution, indium oxide nanopowder and a xylene solution; the thermal expansion coefficients of the ceramic substrate and the non-metallic material are compatible, and the thin film thermocouple is not easy to break;

[0049] The polysilazane in the A electrode and the B electrode is an inorganic polymer material composed of silicon and nitrogen. Polysilazane can form a cross-linked network structure through a thermal curing mechanism. This network structure gives polysilazane excellent heat resistance (temperature resistance can reach above 1600°C), mechanical properties, good high-temperature electrical properties and strong antioxidant properties at high temperatures. It can maintain structural stability under high temperature conditions; the Si-N bond of polysilazane has about 30% ionic bond characteristics, and the Si-N bond energy is relatively small, which makes it easy for the Si-N bond to be transformed into other types of new bonds during the reaction, which helps to form new compounds and enhances the heat resistance and weather resistance of the compounds; these characteristics make the application of polysilazane solution in the production of thermocouple electrodes have potential advantages, especially in sensors that work stably under high temperature environments;

[0050] (2) The present invention uses pulsed laser deposition to prepare the protective layer precursor layer, which can maintain the consistency of the film and protective layer components, and the film components can be controlled by introducing different gases during deposition; in addition, pulsed laser deposition is conducive to accelerating the application of high-performance films in practical scenarios;

[0051] (3) Different from the traditional method of preparing the precursor ceramic film by pyrolysis under protective gases such as argon and nitrogen, the present invention adopts vacuum pyrolysis to prepare the precursor ceramic film thermocouple. On the one hand, vacuum pyrolysis can make the precursor ceramic organic slurry have conductive function, and a conductive sensitive film can be prepared; on the other hand, due to the thermal effect, a greater adhesion force is generated between the film layers. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0053] The structures, proportions, sizes, etc. illustrated in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with the technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantial technical significance. Any structural modification, change in proportion or adjustment of size shall still fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.

[0054] Figure 1 A schematic diagram of the structure of an embodiment of the polymer precursor ceramic thin film thermocouple provided by the present invention applied to a thermal component;

[0055] Figure 2 A schematic diagram of the process flow for preparing a polymer precursor ceramic thin film thermocouple provided by the present invention;

[0056] Figure 3 A schematic diagram of the structure of an embodiment of a pulsed laser deposition system provided by the present invention;

[0057] Figure 4 A schematic diagram of a test curve of three cycles of the polymer precursor ceramic film thermocouple resistance changing with temperature provided by the present invention;

[0058] Figure 5 Schematic diagram of the thermoelectric response output of the polymer precursor ceramic thin film thermocouple provided by the present invention.

[0059] In the figure: 1-substrate; 2-protective layer; 31-A electrode; 32-B electrode; 33-hot node; 34-soldering point; 35-lead; 41-magnetic stirrer; 42-direct writer; 421-storage tube; 422-rod; 51-laser; 52-reflector; 53-converging lens; 6-housing; 61-vacuum chamber; 62-observation window; 63-laser window; 71-substrate; 72-first rotating shaft; 73-first driving motor; 81-target; 82-second rotating shaft; 83-second driving motor. DETAILED DESCRIPTION

[0060] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two, but does not exclude the inclusion of at least one.

[0062] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0063] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0064] In the existing precursor ceramic thin film sensors, the thermal expansion coefficients of the ceramic substrate and the metal material do not match, which makes the thin film temperature sensor easy to fall off; the thin film temperature sensor has poor ability to withstand the impact and vibration load of the engine. Under the impact and vibration, the interface bonding strength between the sensitive layer and the substrate is reduced, and the thin film temperature sensor may break;

[0065] The present invention creatively provides a polymer precursor ceramic thin film thermocouple, comprising an A electrode and a B electrode, wherein the A electrode is made by mixing a polysilazane solution, a nanocomposite material powder and a xylene solution, and the nanocomposite material is made by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; the B electrode is made by mixing a polysilazane solution, an indium oxide nanopowder and a xylene solution;

[0066] Thin film thermocouples are not easy to break, can withstand temperatures above 1600°C, and have excellent high-temperature electrical properties and high-temperature anti-oxidation properties.

[0067] Example 1

[0068] like Figure 1As shown, this embodiment provides a polymer precursor ceramic film thermocouple for monitoring the surface temperature of a hot component; a hot component refers to some high-temperature parts and high-temperature equipment, such as high-temperature components in the fields of aircraft engines, gas turbines, nuclear power devices, and industrial chemical industry, but the application of thermocouples is not limited to these fields. The application of thermocouples to temperature detection of any hot component belongs to the parameters that can be arbitrarily modified by technicians in this field according to different usage scenarios, which belongs to a simple replacement under the technical concept of this embodiment;

[0069] The polymer precursor ceramic thin film thermocouple comprises a substrate 1, a sensitive layer, a protective layer 2, a welding point 34 and a lead 35; the substrate 1 is made of an alumina ceramic sheet, the sensitive layer is arranged on the top surface of the substrate 1, and the protective layer 2 is arranged on the top surface of the sensitive layer; the sensitive layer comprises an A electrode 31 and a B electrode 32 arranged opposite to each other, one end of the A electrode 31 and one end of the B electrode 32 are arranged to intersect and overlap to form a hot node 33; one end of the A electrode 31 away from the hot node 33 and one end of the B electrode 32 away from the hot node 33 are both provided with welding points 34;

[0070] Each welding point 34 is connected to a lead wire 35; the hot node 33 is a temperature measurement point of the polymer precursor ceramic thin film thermocouple, the polymer precursor ceramic thin film thermocouple is connected to a related detection device through the lead wire 35, and the electrical signal of the thermocouple is output through the lead wire 35;

[0071] The polymer precursor ceramic thin film thermocouple of the present application is mainly prepared by polymer precursor ceramics, which are ceramics obtained by vacuum pyrolysis of polymer precursors; the precursor is generally a polymer liquid, which can be given specific properties through molecular design, and its types are rich, and there are many optional materials. After curing, cross-linking and pyrolysis, it becomes a ceramic material; cross-linking and pyrolysis are the processes of decarbonization and dehydrogenation, and some chemical bonds are broken to produce gases such as NH3, H2, and CH4, and the volume shrinkage can reach more than 50%, so it is easy to break, and generally a particle filler method is used to offset the volume shrinkage; the pyrolysis conductivity is very large at 1600°C, and particle fillers can also be added to adjust the performance;

[0072] Therefore, in the present application, the A electrode 31 is made by mixing a polysilazane solution, a nanocomposite powder and a xylene solution in a certain proportion, and the nanocomposite is made by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol in a certain proportion; the chemical formula of the nanocomposite is In 1.35 ZnO 2.11 ; The B electrode 32 is made of a mixture of polysilazane solution, indium oxide nanopowder and xylene solution in a certain proportion; the polymer precursor ceramic thin film thermocouple can withstand a temperature of more than 1600°C and has excellent high-temperature electrical properties and strong anti-oxidation properties;

[0073] Specifically, the A electrode 31 and the B electrode 32 are both L-shaped structures, and the A electrode 31 and the B electrode 32 are combined to form a U-shaped structure.

[0074] Further, in the A electrode 31, the mass fraction of the polysilazane solution is M A1 , the mass fraction of nanocomposite powder is M A2 , the mass fraction of xylene solution is M A3 , M A1 、M A2 and M A3 Satisfaction: 20% ≤ M A1 ≤30%, 20% <M A2 ≤30%, 40%≤M A3 ≤60%; that is, the A electrode 31 is composed of a polysilazane solution, a nanocomposite powder and a xylene solution according to M A1 :M A2 :M A3 The mass ratio is mixed;

[0075] In the B electrode 32, the mass fraction of the polysilazane solution is M B1 , the mass fraction of indium oxide nanopowder is M B2 , the mass fraction of xylene solution is M B3 , M B1 、M B2 and M B3 Satisfaction: 20% ≤ M B1 ≤30%, 20% <M B2 ≤30%, 40%≤M B3 ≤60%; that is, the B electrode 32 is made of polysilazane solution, indium oxide nanopowder and xylene solution according to M B1 :M B2 :M B3 The mass ratio is mixed;

[0076] Preferably, the A electrode 31 is made by mixing a polysilazane solution, a nanocomposite powder and a xylene solution in a mass ratio of 1:1:2; the B electrode 32 is made by mixing a polysilazane solution, an indium oxide nanopowder and a xylene solution in a mass ratio of 1:1:2.

[0077] This embodiment also proposes that in the nanocomposite material, the average particle size of the indium oxide nanopowder is d1, and the average particle size of the zinc oxide powder is d2, and d1 and d2 satisfy: 50nm≤d1≤100nm, 20nm≤d 2≤ 100nm;

[0078] In the B electrode 32, the average particle size of the indium oxide nanopowder is d3, and d3 satisfies: 20nm≤d3≤20um.

[0079] The thickness of the A electrode 31 is H A , the thickness of the B electrode 32 is H B , H A and H B Meet: 2um <H A ≤100um, 2um <H B ≤100um.

[0080] In addition, the solder joint 34 is made by sintering a conductive paste, which is a polysilazane solution filled with titanium diboride nanopowder, and is used to connect the lead 35, which is not easy to fall off after solidification;

[0081] The lead wire 35 is a filamentary structure, the lead wire 35 is a platinum wire and the diameter of the lead wire 35 is d0, d0 satisfies: 160um≤d0≤240um; preferably, d0=200um; the lead wire 35 is used to output the electrical signal of the thermocouple and connect to related detection equipment at the same time, and the length of the lead wire 35 can be adjusted as needed.

[0082] Example 2

[0083] like Figure 2 As shown, based on Example 1, this example proposes a method for preparing a polymer precursor ceramic thin film thermocouple, comprising:

[0084] S1. Pretreatment: washing and drying the alumina ceramic sheet in sequence;

[0085] Specifically, in S1, the length×width×thickness of the alumina ceramic sheet is 80 mm×20 mm×1 mm, and the surface of the alumina ceramic sheet with a size of 80 mm×20 mm×1 mm is ultrasonically cleaned for 15 min using acetone, anhydrous ethanol, and deionized water in sequence, and after cleaning, the surface of the alumina ceramic sheet is blown dry with a nitrogen gun, and then dried at 100°C;

[0086] S2. Preparation of nanocomposite powder: mixing indium oxide nanopowder and zinc oxide powder in a certain proportion, mixing the mixed powder and anhydrous ethanol in a certain proportion and placing the mixed powder in a ball mill tank of a ball mill; controlling the ball mill to grind and drying the mixture to obtain nanocomposite powder;

[0087] Specifically, in S2, indium oxide nanopowder and zinc oxide powder are mixed according to a first preset mass ratio k1; the mixed powder and anhydrous ethanol are mixed according to a second preset mass ratio k2; the speed of the ball mill during grinding is a preset speed n, and the grinding time is a first preset time t1; the temperature during the drying process is a first preset temperature T1;

[0088] Among them, k1, k2, n, t1 and T1 satisfy: 3≤k1≤5, 0.1≤k2≤1, 1600rpm≤n≤2400 rpm, 4h≤t1≤6h, 80℃≤T1≤120℃;

[0089] Preferably, k1=4, k2=0.5, n=2000 rpm, t1=5h, T1=100°C;

[0090] S3, preparation of mixed slurry A and mixed slurry B: polysilazane solution, nanocomposite powder and xylene solution are mixed in proportion to prepare mixed slurry A; polysilazane solution, indium oxide nanopowder and xylene solution are mixed in proportion to prepare mixed slurry B;

[0091] Specifically, in S3, the polysilazane solution, the nanocomposite powder and the xylene solution are mixed according to a third preset mass ratio k3 to obtain a mixed slurry A, and the polysilazane solution, the indium oxide nanopowder and the xylene solution are mixed according to a fourth preset mass ratio k4 to obtain a mixed slurry B; wherein k3 and k4 satisfy: 1:1:3≤k3≤1:1:1, 1:1:3≤k4≤1:1:1; preferably, k3=k4=1:1:2;

[0092] S4, preparation of polymer ceramic precursor A slurry and B slurry: magnetically stirring the A mixed slurry at room temperature by a magnetic stirrer 41 to obtain polymer ceramic precursor A slurry; magnetically stirring the B mixed slurry at room temperature by a magnetic stirrer 41 to obtain polymer ceramic precursor B slurry;

[0093] Specifically, in S4, the magnetic stirring time of the mixed slurry A and the mixed slurry B at room temperature is 120 minutes;

[0094] S5, preparation of the A electrode 31 and the B electrode 32: in a Weisenberg direct writing device, using the Weisenberg (CN110962220B has been disclosed) direct writing process, the polymer precursor ceramic A slurry is directly written on the alumina ceramic sheet, and the polymer precursor ceramic B slurry is directly written on the alumina ceramic sheet; then the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written is placed in a vacuum drying oven for heating and curing treatment, so that the polymer precursor ceramic A slurry and B slurry are cured and cross-linked, and then placed in a vacuum tube furnace for sintering to obtain the A electrode 31 and the B electrode 32;

[0095] Specifically, in S5, the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written thereon is placed in a vacuum drying oven for heating and curing treatment, wherein the temperature during the heating and curing treatment is a second preset temperature T2 and the duration is a second preset duration t2;

[0096] Wherein, T2 and t2 satisfy: 100℃≤T2≤300℃, 0.4h≤t2≤0.6h; preferably, T2=200℃, t2=0.5h;

[0097] The Weissenberg direct writing device includes an XY axis moving platform and a direct writer 42 located above the XY axis moving platform, the direct writer 42 includes a storage tube 421 and a rod 422, a microchannel is formed at the bottom of the storage tube 421, the microchannel is connected to the inside of the storage tube 421, and the microchannel is vertically arranged in the vertical direction; the rod 422 is arranged in the storage tube 421, the bottom of the rod 422 is needle-shaped, the bottom of the rod 422 extends to the outside of the microchannel, and the top of the rod 422 is connected to the DC motor drive; when the direct writing device directly writes a polymer ceramic precursor, the polymer ceramic precursor liquid is injected into the storage tube 421 in advance, the substrate 1 is adhered to the XY axis moving platform, the speed of the DC motor is turned on and adjusted, and the rod 422 rotates at a specific speed in the storage tube 421 to ensure stable liquid supply. The distance between the bottom of the rod 422 and the substrate 1 is adjusted to control the movement of the XY axis moving platform, and the polymer precursor ceramic sensitive film is directly written on the substrate 1;

[0098] The alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written thereon is placed in a vacuum tube furnace for sintering, comprising:

[0099] First, the temperature is raised to a third preset temperature T3 at a preset heating rate v1, and kept at the temperature for a third preset time t3, during which the polymer precursor ceramic slurry A and the polymer precursor ceramic slurry B undergo an organic-to-inorganic transformation and generate an amorphous ceramic;

[0100] Secondly, the temperature is raised to a fourth preset temperature T4 at a preset heating rate v1, and kept at the temperature for a fourth preset time t4, during which the amorphous ceramic undergoes phase separation and crystallization, thereby generating a polycrystalline ceramic;

[0101] Finally, the temperature is lowered to room temperature at a preset cooling rate v2;

[0102] Among them, v1 and v2 meet: 3℃ / min≤v1≤7℃ / min, 3℃ / min≤v2≤7℃ / min; T3 and t3 meet: 900℃≤T3≤1100℃, 3h≤t3≤5h; T4 and t4 meet: 1400℃≤T4≤1800℃; 3h≤t4≤5h;

[0103] Preferably, v1=v2=5°C / min; T3=1000°C, t3=4h, T4=1600°C, t4=4h;

[0104] S6, preparation of solder joint 34: titanium diboride nanopowder and polysilazane solution are mixed according to a fifth preset mass ratio k5 to obtain a conductive paste, the conductive paste is placed on the alumina ceramic sheet and sintered to obtain solder joint 34; solder joint 34 and lead wire 35 are electrically connected and placed in a vacuum tube furnace for sintering; then the temperature is lowered to room temperature and taken out;

[0105] Specifically, in S6, the solder joint 34 and the lead wire 35 are electrically connected and placed in a vacuum tube furnace for sintering at a sixth preset temperature T6 and a sixth preset time t6;

[0106] Among them, k5 satisfies: 1:3≤k5≤1:1; T6 and t6 satisfy: 700℃≤T6≤900℃, 0.5h≤t6≤1.5h;

[0107] Preferably, k5=2:3; T6=800°C, t6=1h;

[0108] S7, preparation of protective layer precursor layer: titanium diboride nanopowder and YSZ nanopowder are mixed according to the sixth preset mass ratio k6 and added to the polysilazane solution, and placed in a vacuum drying oven for heating and curing treatment to obtain a protective layer precursor; the temperature during the heating and curing treatment is the seventh preset temperature T7, and the duration is the seventh preset duration t7; the protective layer precursor has good density and can improve the oxidation resistance of the sensor;

[0109] Specifically, titanium diboride nanopowder and YSZ nanopowder are mixed and added to the polysilazane solution to prepare the protective layer precursor layer, which has the following advantages: ① Enhanced thermal stability: The addition of nanoparticles can improve the thermal stability and high-temperature oxidation resistance of the polysilazane protective layer; ② Improved mechanical properties: The addition of nanoparticles can enhance the mechanical strength and hardness of polysilazane, and the interface between the nanoparticles and the polysilazane matrix can prevent the expansion of cracks, thereby improving the fracture toughness and wear resistance of the material; ③ Improved chemical stability: Nanoparticles can improve the chemical stability of the material and resist corrosion and oxidation; ④ Promote thermal curing reaction: Nanoparticles may act as catalysts or promoters to accelerate the thermal curing reaction of polysilazane, reduce the curing temperature, and shorten the curing time; ⑤ Improved wear resistance: The addition of nanoparticles can increase the roughness and hardness of the material surface, thereby improving wear resistance; ⑥ Enhanced thermal shock resistance: The incorporation of nanoparticles can improve the thermal shock resistance of the material, that is, the ability of the material not to break under rapid temperature changes; ⑦ Optimized electrical properties: The doping of nanoparticles can adjust the conductivity or dielectric properties of polysilazane.

[0110] The protective layer precursor is used as a target material, and is deposited on the top surface of the A electrode 31 and the top surface of the B electrode 32 by pulse laser, and then vacuum pyrolysis is performed to obtain a protective layer precursor layer; during the vacuum pyrolysis, the temperature is increased to the eighth preset temperature T8 at a preset heating rate v1 and kept at the temperature for the eighth preset time t8; it has strong oxidation resistance and can protect the polymer precursor ceramic sensitive film from oxidation;

[0111] Among them, k6 satisfies: 3:1≤k6≤5:1; T7 and t7 satisfy: 100℃≤T7≤300℃, 0.4h≤t7≤0.6h; v1 satisfies: 3℃ / min≤v1≤7℃ / min; T8 and t8 satisfy: 1400℃≤T8≤1800℃, 3h≤t8≤5h;

[0112] Preferably, k6=4:1, T7=200℃, t7=0.5h, v 1= 5℃ / min, T8=1600℃, t8=4h;

[0113] Specifically, in S7, when titanium diboride nanopowder and YSZ nanopowder are added to the polysilazane solution, the mass fraction of titanium diboride nanopowder is 40%, and the average particle size of titanium diboride nanopowder is 50 nm; the mass fraction of YSZ nanopowder is 10%, and the average particle size of YSZ nanopowder is 50 nm;

[0114] Furthermore, the thickness of the protective layer precursor layer is H C , H C Meet: 2um <H C ≤100um;

[0115] Specifically, the use of vacuum heating to cure cross-linked pyrolysis has the following advantages: ① Removal of solvents and volatile components: Heating polysilazane under vacuum conditions can effectively remove solvents and other volatile components, avoiding leaving holes and defects in the material; ② Cross-linking reaction: At a certain temperature, the small molecular fragments produced by decomposition can be recombined to form a three-dimensional network structure through cross-linking reaction. This cross-linking can enhance the mechanical strength and thermal stability of the material; ③ Formation of ceramic phase: As the pyrolysis process continues, the cross-linked network structure is further transformed into an inorganic ceramic phase, such as Si3N4, SiC or SiO2, which The porcelain phase has excellent high-temperature stability and mechanical properties; ④ Stress relief: The vacuum environment helps to reduce the thermal stress generated by the material during the curing process, because there is no atmospheric pressure under vacuum conditions and the material can expand and contract freely; ⑤ Uniform curing: Since there is no oxygen under vacuum conditions, oxidation reactions can be prevented, thereby achieving a more uniform curing process; ⑥ Improve purity: Vacuum heating can reduce the content of impurities in the material and improve the purity and performance of the final product; ⑦ Microstructure control: By precisely controlling the temperature, time and pressure of vacuum heating, the microstructure of the material, such as grain size, porosity and phase composition, can be adjusted.

[0116] like Figure 3As shown, the present embodiment uses a PLD-450 pulsed laser deposition system, which can be roughly divided into several parts: a laser 51, an optical path system, a control panel and a vacuum system; the laser 51 uses a COMPex201F KrF excimer pulse laser, and the optical path system includes a reflector 52 and a converging lens 53. By adjusting the reflector 52 and the converging lens 53, the size and position of the laser spot on the target 81 can be changed; the control panel is used to control some parameters during film deposition, such as vacuum degree, temperature of substrate 71, rotation speed of target 81 and substrate 71, etc.; the vacuum system is the core part of the PLD system, which determines the environment for film growth and the quality of the film; the vacuum system includes a shell 6, a mechanical pump and a molecular pump, a vacuum chamber 61 is formed inside the shell 6, and an observation window 62 and a laser window 63 are formed on the shell wall of the shell 6, the inside of the vacuum chamber 61 can be observed through the observation window 62, and the laser generated by the pulsed laser can enter the vacuum chamber through the laser window 63 61; the mechanical pump is used as a precursor pump of the molecular pump to pump the vacuum degree of the vacuum chamber 61 to less than 0.1 Pa, so as to provide a high vacuum working environment for the molecular pump; the shell wall of the shell 6 is also formed with a first shaft hole and a second shaft hole, the first shaft hole is penetrated by a first rotating shaft 72, and the second shaft hole is penetrated by a second rotating shaft 82; the substrate 71 and the target 81 are both arranged inside the vacuum chamber 61, and the first drive motor 73 and the second drive motor 83 are both arranged outside the vacuum chamber 61; the substrate 71 is arranged at one end of the first rotating shaft 72, and the other end of the first rotating shaft 72 is connected to the first drive motor 73 for driving, and the first drive motor 73 can drive the substrate 71 to rotate when it is running; the target 81 is arranged at one end of the second rotating shaft 82, and the other end of the second rotating shaft 82 is connected to the second drive motor 83 for driving, and the second drive motor 83 can drive the target 81 to rotate; the temperature of the substrate 71 can reach up to 1000°C, the rotation speed of the target 81 and the substrate 71 should not exceed 2rad / s, and the minimum distance between the target 81 and the substrate 71 can be adjusted to 6cm;

[0117] Before deposition, the alumina ceramic sheet with the A electrode 31 and the B electrode 32 directly written thereon is first covered with a mask, and then fixed at the position of the substrate 71, and the substrate 71 is set in the vacuum chamber 61 and connected to the first rotating shaft 72; similarly, the target 81 is set in the vacuum chamber 61 and connected to the second rotating shaft 82. Pulsed laser deposition requires a high vacuum film growth environment. First, turn on the mechanical pump to pump the vacuum degree to below 10Pa, and then turn on the cooling water and molecular pump (the function of the cooling water is to prevent the molecular pump from being damaged due to excessive operating temperature). When the vacuum degree is less than 5×10 -4 Pa can start deposition, and the deposition time is 40min. Before depositing the film, the target material 81 needs to be pre-sputtered for about 10min to remove contaminants on the surface of the target material 81;

[0118] The pulse laser 51 emits laser light, which enters the vacuum chamber 61 through the reflector 52, the converging lens 53 and the laser window 63, and is focused on the target 81. The surface of the target 81 is instantly heated, melted, and vaporized to generate high-temperature and high-pressure plasma. Then, the plasma is transmitted from the target 81 to the substrate 71 to form a plume, and grows on the alumina ceramic sheet with the A electrode 31 and the B electrode 32 directly written thereon to form a protective film.

[0119] As the temperature of the substrate 71 increases, the particles excited by the laser move to the substrate 71 and can obtain enough energy to migrate along the surface and combine with other particles to form grains, so the growth rate of the film is accelerated; as the deposition rate of the film continues to increase, the film thickness also increases accordingly;

[0120] After the preparation is completed, the polymer precursor ceramic thin film thermocouple is tested from room temperature to 1600°C. One end of the thin film thermocouple hot node 33 is placed in a high-temperature furnace, and a standard S-type thermocouple is placed just above the hot node 33 on the same cross section to synchronously measure the temperature at the hot node 33; the thermocouple cold node (welding point 34) is placed on a water-cooled table, and a K-type thermocouple is placed at the same level as the cold node to synchronously measure the cold end temperature; the resistance voltage output of the thermocouple and the temperatures measured by the two thermocouples at the hot and cold nodes are synchronously acquired through a multifunctional data acquisition system;

[0121] The use of pulsed laser deposition of the protective layer precursor layer has the following advantages: ① High composition preservation: PLD technology can produce thin films with the same composition as the target material; ② High deposition rate: Compared with other deposition processes, PLD technology has a rapid reaction and a high deposition rate; ③ Strong directionality: PLD technology has good directionality, high film deposition resolution, and is easy to achieve micro-area deposition, so as to prepare functional films with fine grain size and fine microstructure; ④ Deposition of materials with complex chemical composition: PLD technology can perform full equivalent coating on composite materials with complex chemical composition; ⑤ Wide range of applications: PLD technology can prepare almost all thin film materials, and has great development potential and broad application prospects; ⑥ Low temperature deposition: PLD technology can be deposited at a lower temperature, which is very useful for materials and substrates that need to avoid the influence of high temperature; ⑦ Application of ultrashort pulse laser: Ultrashort pulse laser has extremely high peak power, and the generated ion kinetic energy is high and easy to finely control, so that nano-films with unique structures can be prepared; ⑧ Combination with other deposition technologies: PLD technology can be combined with other deposition methods to form a new film preparation technology to further improve the quality of the film.

[0122] The resistance variation of the polymer precursor ceramic thin film thermocouple at 0°C to 1600°C was tested with the following dimensions: the length×width×thickness of the alumina ceramic sheet was 80mm×20mm×1mm, the length×width×thickness of the A electrode 31 and the B electrode 32 were both 74mm×3mm×10μm, and the test conditions during the test were as follows: the temperature of the cold node was kept at 0°C, the initial temperature of the hot node was set to 0°C, and the test was performed every 50°C until the temperature of the hot node reached 1600°C; Figure 4 is a test curve of three cycles of resistance variation with temperature of the polymer precursor ceramic thin film thermocouple from 0 to 1600°C, Figure 4 It can be seen that the polymer precursor ceramic thin film thermocouple prepared by the present invention has good repeatability, excellent high-temperature electrical properties, strong anti-oxidation properties, and can work well at 1600°C, which means that the thin film thermocouple does not break and the film layers have great adhesion.

[0123] The thermoelectric response output of the polymer precursor ceramic thin film thermocouple of the present invention from room temperature to 1600°C was tested. The dimensions of the thermocouple during the test are as follows: the length×width×thickness of the alumina ceramic sheet is 80mm×20mm×1mm, the length×width×thickness of the A electrode 31 and the B electrode 32 are both 74mm×3mm×10μm, and the test conditions during the test are as follows: the temperature of the cold node is maintained at 20°C, the initial temperature of the hot node is set to 20°C, and the simulation is performed every 50°C until the temperature of the hot node reaches 1600°C; Figure 5 The thermoelectric response of the polymer precursor ceramic film thermocouple is measured by Figure 5 It can be seen that the polymer precursor ceramic thin film thermocouple prepared in the present invention has very good repetitive characteristics and very stable output. The maximum output voltage is 84.6mV and the Seebeck coefficient is about 55.8uV / °C, which means that the thin film thermocouple is not broken and the film layers have great adhesion.

[0124] In summary, in terms of materials, the polymer precursor ceramic thin film thermocouple includes an A electrode 31 and a B electrode 32, wherein the A electrode 31 is made by mixing a polysilazane solution, a nanocomposite material powder and a xylene solution, and the nanocomposite material is made by mixing indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; the B electrode 32 is made by mixing a polysilazane solution, indium oxide nanopowder and a xylene solution; in terms of structure, in the preparation of the protective layer precursor layer, titanium diboride nanopowder and YSZ nanopowder are added to the polysilazane solution and mixed, and a protective layer precursor is obtained after vacuum heating and curing treatment; the protective layer precursor is used as a target material, and is deposited on the top surface of the A electrode 31 and the top surface of the B electrode 32 by pulsed laser, and is obtained after vacuum pyrolysis. layer, which has strong antioxidant properties and can protect the polymer precursor ceramic sensitive film from being oxidized; in terms of process, the Weissenberg direct writing process is adopted to directly write the polymer precursor ceramic A slurry on the alumina ceramic sheet, and the polymer precursor ceramic B slurry is directly written on the alumina ceramic sheet, and then placed in a vacuum drying oven for heating to make the polymer precursor ceramic A slurry and B slurry solidify and cross-link, and finally placed in a vacuum tube furnace for sintering to obtain the A electrode 31 and the B electrode 32; the protective layer precursor layer is made by pulsed laser deposition, which can maintain the consistency of the film and protective layer components; on the one hand, vacuum pyrolysis can make the precursor ceramic organic slurry have conductive function, and a conductive sensitive film can be obtained; on the other hand, due to the thermal effect, a greater adhesion is generated between the film layers.

[0125] Example 3

[0126] Based on Example 1, this example proposes a method for preparing a polymer precursor ceramic thin film thermocouple, comprising:

[0127] S1. Pretreatment: washing and drying the alumina ceramic sheet in sequence;

[0128] Specifically, in S1, the length×width×thickness of the alumina ceramic sheet is 80 mm×20 mm×1 mm, and the surface of the alumina ceramic sheet with a size of 80 mm×20 mm×1 mm is ultrasonically cleaned for 15 min using acetone, anhydrous ethanol, and deionized water in sequence, and after cleaning, the surface of the alumina ceramic sheet is blown dry with a nitrogen gun, and then dried at 100°C;

[0129] S2. Preparation of nanocomposite powder: mixing indium oxide nanopowder and zinc oxide powder in a certain proportion, mixing the mixed powder and anhydrous ethanol in a certain proportion and placing the mixed powder in a ball mill tank of a ball mill; controlling the ball mill to grind and drying the mixture to obtain nanocomposite powder;

[0130] Specifically, in S2, indium oxide nanopowder and zinc oxide powder are mixed according to a first preset mass ratio k1; the mixed powder and anhydrous ethanol are mixed according to a second preset mass ratio k2; the speed of the ball mill during grinding is a preset speed n, and the grinding time is a first preset time t1; the temperature during the drying process is a first preset temperature T1;

[0131] Among them, k1, k2, n, t1 and T1 satisfy: 3≤k1≤5, 0.1≤k2≤1, 1600rpm≤n≤2400 rpm, 4h≤t1≤6h, 100℃≤T1≤120℃;

[0132] Preferably, k1=4, k2=0.5, n=2000 rpm, t1=5h, T1=100°C;

[0133] S3, preparation of mixed slurry A and mixed slurry B: polysilazane solution, nanocomposite powder and xylene solution are mixed in proportion to prepare mixed slurry A; polysilazane solution, indium oxide nanopowder and xylene solution are mixed in proportion to prepare mixed slurry B;

[0134] Specifically, in S3, the polysilazane solution, the nanocomposite powder and the xylene solution are mixed according to a third preset mass ratio k3 to obtain a mixed slurry A, and the polysilazane solution, the indium oxide nanopowder and the xylene solution are mixed according to a fourth preset mass ratio k4 to obtain a mixed slurry B; wherein k3 and k4 satisfy: 1:1:3≤k3≤1:1:1, 1:1:3≤k4≤1:1:1; preferably, k3=k4=1:1:2;

[0135] S4, preparation of polymer ceramic precursor A slurry and B slurry: magnetically stirring the A mixed slurry at room temperature by a magnetic stirrer 41 to obtain polymer ceramic precursor A slurry; magnetically stirring the B mixed slurry at room temperature by a magnetic stirrer 41 to obtain polymer ceramic precursor B slurry;

[0136] Specifically, in S4, the magnetic stirring time of the mixed slurry A and the mixed slurry B at room temperature is 120 minutes;

[0137] S5, preparation of the A electrode 31 and the B electrode 32: in a Weisenberg direct writing device, using the Weisenberg (CN110962220B has been disclosed) direct writing process, the polymer precursor ceramic A slurry is directly written on the alumina ceramic sheet, and the polymer precursor ceramic B slurry is directly written on the alumina ceramic sheet; then the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written is placed in a vacuum drying oven for heating and curing treatment, so that the polymer precursor ceramic A slurry and B slurry are cured and cross-linked, and then placed in a vacuum tube furnace for sintering to obtain the A electrode 31 and the B electrode 32;

[0138] Specifically, in S5, the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written thereon is placed in a vacuum drying oven for heating and curing treatment, wherein the temperature during the heating and curing treatment is a second preset temperature T2 and the duration is a second preset duration t2;

[0139] Among them, T2 and t2 meet the following conditions: 100℃≤T2≤300℃, 0.4h≤t2≤0.6h;

[0140] Preferably, T2=200°C, t2=0.5h;

[0141] The alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written thereon is placed in a vacuum tube furnace for sintering, comprising:

[0142] First, the temperature is raised to a third preset temperature T3 at a preset heating rate v1, and kept at the temperature for a third preset time t3, during which the polymer precursor ceramic slurry A and the polymer precursor ceramic slurry B undergo an organic-to-inorganic transformation and generate an amorphous ceramic;

[0143] Secondly, the temperature is raised to a fourth preset temperature T4 at a preset heating rate v1, and kept at the temperature for a fourth preset time t4, during which the amorphous ceramic undergoes phase separation and crystallization, thereby generating a polycrystalline ceramic;

[0144] Finally, the temperature is lowered to 1200°C at a preset cooling rate v2 for annealing;

[0145] Among them, v1 and v2 meet: 3℃ / min≤v1≤7℃ / min, 3℃ / min≤v2≤7℃ / min; T3 and t3 meet: 900℃≤T3≤1100℃, 3h≤t3≤5h; T4 and t4 meet: 1400℃≤T4≤1800℃; 3h≤t4≤5h;

[0146] Preferably, v1=v2=5°C / min; T3=1000°C, t3=4h, T4=1600°C, t4=4h;

[0147] S6. Preparation of protective layer precursor layer: placing the ceramic sheet with the polymer precursor ceramic sensitive film in a vacuum tube furnace for a long time at high temperature for annealing treatment, so that the polymer precursor ceramic film forms a more stable oxidation phase to protect the unoxidized part below, cooling to room temperature and taking out; the temperature during the annealing treatment is the ninth preset temperature T9, and the duration is the ninth preset duration t9;

[0148] Among them, T9 and t9 meet the following conditions: 1000℃≤T9≤1400℃, 8h≤t9≤12h;

[0149] Preferably, T9=1200°C, t9=10h;

[0150] Specifically, the polymer precursor is directly annealed to form a layer of stable oxide phase, which has the following advantages: ① Crystal growth: As the annealing temperature further increases, the formed oxide phase may undergo a crystal growth process to form a more ordered crystal structure, thereby improving the hardness and stability of the material; ② Densification: During the annealing process, the material may undergo densification, that is, the porosity is reduced and the density is increased, which helps to improve the mechanical strength and chemical corrosion resistance of the material; ③ Stress release: During the heat treatment process, due to the difference in thermal expansion coefficients, stress may be generated between the polymer precursor and the formed oxide. Appropriate annealing can release these stresses and prevent the material from cracking; ④ Surface and interface optimization: The annealing process can improve the surface and interface properties of the material, thereby improving the overall performance of the material.

[0151] S7, preparation of solder joint 34: titanium diboride nanopowder and polysilazane solution are mixed according to a fifth preset mass ratio k5 to obtain a conductive paste, the conductive paste is placed on the alumina ceramic sheet and sintered to obtain solder joint 34; solder joint 34 and lead 35 are electrically connected and placed in a vacuum tube furnace for sintering, cooled to room temperature and taken out;

[0152] The solder joint 34 and the lead wire 35 are electrically connected and placed in a vacuum tube furnace for sintering at a temperature of a sixth preset temperature T6 and a time period of a sixth preset time period t6;

[0153] Among them, k5 satisfies: 1:3≤k5≤1:1, T6 and t6 satisfy: 700℃≤T6≤900℃, 0.5h≤t6≤1.5h;

[0154] Preferably, k5=2:3; T6=800°C, t6=1h.

[0155] In summary, different from the traditional method of preparing the precursor ceramic film by pyrolysis under protective gases such as argon and nitrogen, the present invention uses vacuum pyrolysis to prepare the precursor ceramic film thermocouple. On the one hand, vacuum pyrolysis can make the precursor ceramic organic slurry have conductive function, and a conductive sensitive film can be prepared; on the other hand, due to the thermal effect, a greater adhesion force is generated between the film layers.

[0156] The exemplary embodiments of the present disclosure are specifically shown and described above. It should be understood that the present disclosure is not limited to the detailed structures, configurations or implementations described herein; on the contrary, the present disclosure is intended to cover various modifications and equivalent configurations included in the spirit and scope of the appended claims.

Claims

1. A method for preparing a polymer precursor ceramic thin film thermocouple for monitoring the surface temperature of a hot component; characterized in that: The polymer precursor ceramic thin film thermocouple comprises an A electrode (31) and a B electrode (32), one end of the A electrode (31) and one end of the B electrode (32) are arranged to intersect and overlap to form a hot node (33), and one end of the A electrode (31) away from the hot node (33) and one end of the B electrode (32) away from the hot node (33) are both provided with a welding point (34); the A electrode (31) is made of a mixture of a polysilazane solution, a nanocomposite material powder and a xylene solution; the B electrode (32) is made of a mixture of a polysilazane solution, an indium oxide nanopowder and a xylene solution; wherein the nanocomposite material is made of a mixture of indium oxide nanopowder, zinc oxide powder and anhydrous ethanol; each of the welding points (34) is connected to a lead wire (35), and the lead wire (35) is used to output a signal; the preparation method comprises: S1. Pretreatment: cleaning and drying the alumina ceramic sheet; S2, preparation of the nanocomposite powder: mixing the indium oxide nanopowder and the zinc oxide powder according to a first preset mass ratio k1, mixing the mixed powder and anhydrous ethanol according to a second preset mass ratio k2 and placing the mixed powder in a ball mill tank of a ball mill; controlling the ball mill to grind, and drying the mixture to obtain the nanocomposite powder; the speed of the ball mill during grinding is a preset speed n, and the grinding time is a first preset time t1; the temperature during the drying process is a first preset temperature T1; Wherein, the k1, k2, n, t1 and T1 satisfy: 3≤k1≤5, 0.1≤k2≤1, 1600rpm≤n≤2400 rpm, 4h≤t1≤6h, 80℃≤T1≤120℃; S3, preparation of mixed slurry A and mixed slurry B: the polysilazane solution, the nanocomposite powder and the xylene solution are mixed according to a third preset mass ratio k3 to prepare mixed slurry A; the polysilazane solution, the indium oxide nanopowder and the xylene solution are mixed according to a fourth preset mass ratio k4 to prepare mixed slurry B; Wherein, k3 and k4 satisfy: 1:1:3≤k3≤1:1:1, 1:1:3≤k4≤1:1:1; S4, preparation of polymer ceramic precursor A slurry and B slurry: magnetically stirring the A mixed slurry at room temperature to obtain polymer ceramic precursor A slurry; magnetically stirring the B mixed slurry at room temperature to obtain polymer ceramic precursor B slurry; S5, preparation of the A electrode (31) and the B electrode (32): using the Weissenberg direct writing process, directly writing the polymer precursor ceramic A slurry on the alumina ceramic sheet, and directly writing the polymer precursor ceramic B slurry on the alumina ceramic sheet; then placing the alumina ceramic sheet with the polymer precursor ceramic A slurry and B slurry directly written in a vacuum drying oven for heating and curing treatment, and then placing it in a vacuum tube furnace for sintering to obtain the A electrode (31) and the B electrode (32); In S5, placing the alumina ceramic sheet on which the polymer precursor ceramic A slurry and B slurry are directly written in a vacuum tube furnace for sintering comprises: First, the temperature is raised to a third preset temperature T3 at a preset heating rate v1, and kept at the temperature for a third preset time t3, during which the polymer precursor ceramic slurry A and the polymer precursor ceramic slurry B undergo an organic-to-inorganic transformation and generate an amorphous ceramic; Secondly, the temperature is raised to a fourth preset temperature T4 at a preset heating rate v1, and kept at the temperature for a fourth preset time t4, during which the amorphous ceramic undergoes phase separation and crystallization, thereby generating a polycrystalline ceramic; Finally, the temperature is lowered to room temperature at a preset cooling rate v2; Wherein, the v1 and v2 satisfy: 3℃ / min≤v1≤7℃ / min, 3℃ / min≤v2≤7℃ / min; the T3 and t3 satisfy: 900℃≤T3≤1100℃, 3h≤t3≤5h; the T4 and t4 satisfy: 1400℃≤T4≤1800℃; 3h≤t4≤5h; S6, preparation of the solder joint (34): mixing titanium diboride nanopowder and polysilazane solution according to a fifth preset mass ratio k5 to obtain a conductive paste, placing the conductive paste on the alumina ceramic sheet and sintering to obtain the solder joint (34); electrically connecting the solder joint (34) and the lead wire (35) and placing them in a vacuum tube furnace for sintering; wherein k5 satisfies: 1:3≤k5≤1:1; S7, preparation of a protective layer precursor layer: titanium diboride nanopowder and YSZ nanopowder are mixed according to a sixth preset mass ratio k6 and added to a polysilazane solution, and placed in a vacuum drying oven for heat curing treatment to obtain a protective layer precursor; the temperature during the heat curing treatment is the seventh preset temperature T7, and the duration is the seventh preset duration t7; First, an alumina ceramic sheet with an A electrode (31) and a B electrode (32) directly written thereon is covered with a mask, a protective layer precursor is used as a target material, and a pulsed laser is used to deposit the protective layer precursor on the top surface of the A electrode (31) and the top surface of the B electrode (32), and then vacuum pyrolysis is performed to obtain a protective layer precursor layer; during the vacuum pyrolysis, the temperature is increased to an eighth preset temperature T8 at a preset heating rate v1 and maintained at the temperature for an eighth preset time t8; Among them, the k6 satisfies: 3:1≤k6≤5:1; the T7 and t7 satisfy: 100℃≤T7≤300℃, 0.4h≤t7≤0.6h; the v1 satisfies: 3℃ / min≤v1≤7℃ / min; the T8 and t8 satisfy: 1400℃≤T8≤1800℃, 3h≤t8≤5h.

2. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 1, characterized in that: In the nanocomposite material, the average particle size of the indium oxide nanopowder is d1, the average particle size of the zinc oxide powder is d2, and d1 and d2 satisfy: 50nm≤d1≤100nm, 20nm≤d2≤100nm; In the B electrode (32), the average particle size of the indium oxide nanopowder is d3, and d3 satisfies: 20nm≤d3≤20um; The thickness of the A electrode (31) is H A The thickness of the B electrode (32) is H B , the H A and H B Meet: 2um <H A ≤100um, 2um <H B ≤100um.

3. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 1, characterized in that: The lead wire (35) is a filamentous structure, the lead wire (35) is a platinum wire, and the diameter of the lead wire (35) is d0, and d0 satisfies: 160um≤d0≤240um.

4. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 1, characterized in that: In S5, the alumina ceramic sheet on which the polymer precursor ceramic A slurry and B slurry are directly written is placed in a vacuum drying oven for heating and curing treatment, and the temperature during the heating and curing treatment is a second preset temperature T2 and the duration is a second preset duration t2; Wherein, T2 and t2 satisfy: 100°C≤T2≤300°C, 0.4h≤t2≤0.6h.

5. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 4, characterized in that: The S5 further includes: Placing the alumina ceramic sheet on which the A electrode (31) and the B electrode (32) are directly written in a vacuum tube furnace for annealing treatment, so that a layer of oxidation phase is formed on the surface of the A electrode (31) and the surface of the B electrode (32); the temperature during the annealing treatment is a fifth preset temperature T5, and the duration is a fifth preset duration t5; Wherein, the T5 and t5 satisfy: 1000°C≤T5≤1400°C, 8h≤t5≤12h.

6. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 1, characterized in that: In S6, the solder joint (34) and the lead wire (35) are electrically connected and placed in a vacuum tube furnace for sintering at a temperature of a sixth preset temperature T6 and a time period of a sixth preset time period t6; Wherein, T6 and t6 satisfy: 700°C≤T6≤900°C, 0.5h≤t6≤1.5h.

7. The method for preparing a polymer precursor ceramic thin film thermocouple according to claim 1, characterized in that: The thickness of the protective layer precursor layer is H C , the H C Meet: 2um <H C ≤100um.

Citation Information

Patent Citations

  • A direct writing device and fabrication method for polymer precursor ceramic thin films

    CN110962220B

  • Thin film thermocouple based on indium oxide composite material and preparation method thereof

    CN113959574A

  • Polymer precursor ceramic film thermocouple and manufacturing method thereof

    CN115628820A

  • Preparation method of polymer precursor ceramic high-temperature film sensor

    CN118439869A